Konsumsi Zat Besi yang Adekuat selama Hamil untuk Cegah Bayi Lahir dengan Stunting: Adequate Iron Consumption during Pregnancy to Prevent Babies Born with Stunting - Hermawan, Dessy; Listyaningsih, Erna; Irianto, Gunawan; Sary, Lolita; Shariff, Fonda Octarianingsih; Kurnisari, Devi; Reni, Christina Kusuma (Universitas Airlangga, 2025)
Background: The incidence of stunting remained high until 2024, namely 21.6%, making it a national problem. Stunting can be predicted early by using the length of the birth body. However, many people do not care about the length of the baby's body at birth. Many factors affect the length of the baby's body at birth, including genetic and external factors. Anemia in pregnant women is one of the determining factors for stunting, so giving iron tablets is very important to prevent stunting. Objectives: The purpose of this study was to analyze the relationship between iron tablet consumption and the baby's length at birth. Methods: This study was an analytical survey that examines the characteristics of mothers who have live-born babies with mature in 2019 to 2023 in Tugurejo Village. Data were collected from records in the Mother and Child Health/MCH book and direct interviews with research subjects. The number of samples was 108 babies and their mothers. The collected data were analyzed using chi square & logistic regression tests. Results: There was a significant relationship between taboo from consuming one source of protein (p-value=0.034), consumption of iron tablets during pregnancy (p-value=0.043), maternal age during pregnancy (p-value=0.001), and exposure to cigarette smoke during pregnancy (p-value=0.050) with baby's birth length. Meanwhile, the mother's height and the habit of drinking milk during pregnancy were not significantly related to the baby's birth length. Conclusions: The dominant variables related to the length of the baby's birth are the completeness of iron tablet consumption and the mother's age during pregnancy.